Pathways between BMI and adherence to weight management in adolescence - Prioste, Ana (2018)
Background: In order to understand the mechanisms involved in how overweight adolescents adhere to weight management and perceive its benefits, a few variables have been identified, namely, body mass index (BMI), body self-esteem (BSE) and positive perspective of life (PPL). Methods: In a sample of 112 adolescents, we investigated whether BMI would predict adolescents’ self-efficacy/adherence (SEA) to weight management and perception of its benefits. A structural equation modeling approach was chosen. We hypothesized that perceived quality of life (PQL) would mediate the relationships between BMI and SEA and between BMI and perception of benefits (PB). Results: The results suggested that BMI is not directly associated with SEA and PB. However, PQL was identified as a mediator between BMI and SEA and PB. Conclusion: These findings bring important implications for understanding overweight adolescents’ adherence to weight management. There is evidence that adolescents’ adherence to weight management and PB are not predicted by their BMI. However, it has been shown that PQL mediates this process. For a long time, health professionals have been too focused on BMI. Time has come to be more focused on quality of life and how to improve it.